Uma abordagem matemática no ensino da robótica - Queiroz, Paula Caroline Lopes Custodio (2024)
The objective of this research is to present a proposal on how robotics can contribute to the teaching of mathematics today. To this end, we discuss the trajectory of educational robotics and propose a set of activities for robotics classes integrated with mathematical concepts, highlighting the possibilities of addressing mathematics content in the 3rd, 4th, and 5th grades of Elementary School. In addition, alternative activities with diverse materials are suggested, thus ensuring access for all schools. The activities presented exemplify the potential of robotics in teaching mathematics, combining specific robotics materials with other resources, thereby promoting a comprehensive learning experience.